Exploring nutritional risks of the specific carbohydrate diet: food and nutrient intake in children with juvenile idiopathic arthritis - Naima Hagström; Afsaneh Koochek; Eva Warensjö Lemming; Anders Öman; Henrik Arnell; Lillemor Berntson (Journal of Nutritional Science)
Diet is considered a key research priority for juvenile idiopathic arthritis (JIA), garnering considerable interest from affected families. Despite this, research studies focusing on dietary interventions remain scarce. The specific carbohydrate diet (SCD) has shown potential, however, its nutritional consequences and risks are not well understood. This study aims to describe and evaluate food and nutrient intakes in children with JIA adhering to the SCD and contextualize the results relative to recommendations and intakes in the general population. In a secondary analysis, food and nutrient intakes from three-day dietary records of ten children, following a four-week SCD intervention, were evaluated against the Nordic Nutrition Recommendations 2023 and Riksmaten Adolescents data (RMA) (n = 1282). All children following the SCD met the recommended minimum intake of fruit and vegetables of 500g/day, a stark contrast to the 6% in RMA. Median dietary fibre intake for the SCD was 26g/d, (IQR 21-33), compared to 16g/d (IQR 12-22) in RMA. Elevated saturated fatty acid (SFA) intake was observed in both groups, with the SCD group also consuming high amounts of red meat. Calcium was the sole nutrient for which the standard diet surpassed the SCD, as 9 out of 10 participants had inadequate intake. While children on the SCD showed a lower likelihood of nutrient inadequacy compared to the general population, inadequate calcium intake and elevated SFA and red meat consumption are concerning given known comorbidities in JIA. These results highlight the importance of disease-specific dietary guidance to ensure optimal support for patients and parents.